Wizbook gets an automatic upgrade Red Fox Wizbook1020i. - Oliveros, Luis Anthony G. (PC World Philippines)
While it isn't exactly groundbreaking when it comes to its specs, features and most importantly, its borderline nondescript appearance, it's not bad either. In fact, the Red Fox Wizbook1020i sits tightly up there as one of the better netbooks we've tested so far, and it's just right for its sub-P20,00 price tag.